2020
DOI: 10.1093/ve/veaa024
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic sampling of wild native and invasive birds reveals a rich diversity of adenoviruses in Australia

Abstract: Little is known about the diversity of adenoviruses in wild birds and how they have evolved and are maintained in complex ecosystems. In this study, 409 samples were collected from woodland birds caught for banding (droppings), birds submitted to a wildlife hospital (droppings and tissues), silver gulls (droppings or tissues), and feral pigeons (Columbia livia; oral, cloacal swabs, or tissues) from the Greater Sydney area in NSW, Australia. Additional samples were from native pigeons and doves (swabs) presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 56 publications
2
50
0
Order By: Relevance
“…Similar to the balanced G+C contents in reptilian atadenoviruses and PsAdV-3 genome sequence [ 5 , 10 , 11 ], the novel PaAdV-1 genome sequence also showed a balanced G+C content (53.70), in contrast to the G+C content seen with most of the of avian and ruminant atadenoviruses ( Table 2 ). Interestingly, a very recent study has shown that the greatest diversity existed in the G+C contents in partial DNA polymerase gene of atadenoviruses that was originally sequenced from similar species of birds [ 4 ]. This scenario highlights that the low G+C content is not likely a consistent feature of the genus Atadenovirus , and it would be reasonable to take careful consideration to distinguish relatively closely related viruses based on G+C contents.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar to the balanced G+C contents in reptilian atadenoviruses and PsAdV-3 genome sequence [ 5 , 10 , 11 ], the novel PaAdV-1 genome sequence also showed a balanced G+C content (53.70), in contrast to the G+C content seen with most of the of avian and ruminant atadenoviruses ( Table 2 ). Interestingly, a very recent study has shown that the greatest diversity existed in the G+C contents in partial DNA polymerase gene of atadenoviruses that was originally sequenced from similar species of birds [ 4 ]. This scenario highlights that the low G+C content is not likely a consistent feature of the genus Atadenovirus , and it would be reasonable to take careful consideration to distinguish relatively closely related viruses based on G+C contents.…”
Section: Discussionmentioning
confidence: 99%
“…The total genomic DNA was extracted from collected droppings, using a commercial kit (PurelinkTM Genomic DNA Mini Kit, Invitrogen, California, CA, USA) according to the manufacturer’s instructions. Initially, the extracted DNA was screened for the presence of adenoviruses, using an established PCR protocol that has been widely used to detect adenoviruses, and, based on a short amino acid sequence of the DNA polymerase gene, it was found to be an atadenovirus whose sequence clustered with atadenoviruses derived from other Australian passerine species [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Novel DNA sequences identified from four of the adenovirus genera (Aviadenovirus, Atadenovirus, Siadenovirus, and Mastadenovirus) have important implications for our understanding of adenovirus history and evolution [33].…”
Section: Discussionmentioning
confidence: 99%